Carta de Manuel Guzmán Rodríguez a Roberto H. Todd - Guzmán Rodríguez, Manuel; Todd, Roberto H. (My University, 1929)
Varios anécdotas de José Julio Henna.
Keywords: Guzmán Rodríguez, Manuel--Correspondence.; Guzmán Rodríguez, Manuel--Correspondencia.; Todd, Roberto H.--Correspondence.; Todd, Roberto H.--Correspondencia.; Henna, José Julio, 1848-1924